Development of an Augmented Reality-Based Practicum E-Module Integrated with Local Wisdom of Salak Fruit - Pohan, Heni Mulyani; Syaputra, Adi; Harahap, Fatma Suryani; Yunita, Dinda; Siregar, Rabiyatul Adawiyah; Mabrouk, Anouar Ben (Jurnal Tadris Kimiya, 2024)
The integration of augmented reality (AR) technology into education has gained attention as an innovative tool to enhance students' learning experiences, particularly for abstract concepts such as chemical bonding. E-modules that incorporate AR can provide three-dimensional visualizations, making complex topics more accessible and engaging. This study aims to develop and validate practical e-modules using AR technology to enhance students' spatial intelligence while incorporating local wisdom from Padangsidimpuan. The research follows a Research and Development (R&D) approach using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model and a pretest-posttest control group design. Data were collected from three high schools in Padangsidimpuan using simple random sampling. Instruments included validation sheets (for material, media, and language), observation, user response questionnaires, and pretest-posttest tests to assess students' spatial intelligence. The e-module achieved high validation scores: 0.9 (material), 0.8 (media), and 0.9 (language). Student response rates were 80% (feasibility), 85% (AR usage), and 83.2% (language). Teachers provided an average response score of 88.6, indicating high practicality. The spatial intelligence assessment across the three schools yielded an average score of 0.85 in the high category. The AR-based e-modules effectively improve students' spatial intelligence by visualizing abstract chemical bonding concepts in 3D. This innovation contributes to enhancing chemistry education and preserving local wisdom in Padangsidimpuan, offering a model for future educational advancements.